Total endovascular arch repair: Initial experience in BolognaCentral MessagePerspective - Luca Di Marco, MD, PhD; Chiara Nocera, MD, PhD; Francesco Buia, MD; Francesco Campanini, MD; Domenico Attinà, MD; Giacomo Murana, MD; Luigi Lovato, MD; Davide Pacini, MD, PhD (JTCVS Techniques)
Objectives: In the last few years, fenestrated, branched, or scalloped custom grafts have become available for aortic arch repair. Open surgery is the gold standard, but arch thoracic endovascular aortic repair (TEVAR) is indicated for high-risk patients. We focused on total endovascular aortic arch replacement with a zone 0 or zone 1 landing zone to describe its short- and long-term outcomes. Methods: We retrospectively analyzed patients who underwent arch TEVAR with a zone 0 or zone 1 landing zone at our center. We then performed a Kaplan-Meier analysis for survival and freedom from reintervention at follow-up. Results: From May 2017 to November 2023, 15 patients underwent elective arch TEVAR, having been deemed unfit for open surgery. Mean age was 74.7 ± 7.8 years. The most frequent procedure was fenestrated endovascular aortic repair with a left carotid-subclavian bypass (LCSB) (6; 40%), followed by double-branched graft with LCSB (5; 33.3%) and triple-branched graft (2; 13.3%) and scalloped graft with LCSB (2; 13.3%). There was 1 in-hospital death (6.7%). Perioperative stroke occurred in 2 cases (13.3%). Mean follow-up (FU) time was 16.4 ± 15.1 months. There were 3 deaths at FU, all for noncardiovascular causes, and 1 stroke at FU. One patient required further stenting of the brachiocephalic trunk for a type III endoleak. Survival at 12 months was 87.5% and freedom from reintervention was 85.7%. Conclusions: Total endovascular aortic arch repair with custom-made prosthesis is a safe and effective procedure in patients with prohibitive surgical risk. Stroke remains the main complication with significant rates.